BELARUSIAN EMIGRANT STUDENT ORGANIZATIONS IN CZECHOSLOVAKIA (1921–1939) (Південний архів (історичні науки), 2022)
The purpose of the work. The article is devoted to the analysis of Belarusian student organizations on the territory of Czechoslovakia in 1921–1939. Methods. The main focus is on the activities of Belarusian student organizations in line with the pan-European student movement. Using the method of synthesis, it was established that the student, despite the diversity of the Belarusian movement, he still stood in the same position (except for communist students). This was manifested primarily in the creation of a super-organization – the Association of Belarusian Student Organizations, which gave the opportunity to conduct global international work (activities in the International Student Confederation, participation in various assemblies and meetings). During the study of organizations, the historical method was used to determine not only the reasons and prerequisites for their creation, but also further activities. Results and scientific novelty of the study. The reasons for the formation of Czechoslovakia as a Belarusian student center in the study period are identified. The number, political orientation and activities of each of the associations were analyzed. At the corner of Belarusian student organizations, the influence of Czechoslovakia’s policy on migrants, a clear example of which was the “Russian action” of the Czechoslovak government, was not ruled out. Relationships with representatives of other diasporas have been identified. Conclusions. It is proved that despite the challenges he faced, Belarusian students were quite active, especially on the international stage. It also did not stay away from the general diaspora activities of Belarusians, first of all, actively reacting to the events in the environment of political emigration.
Keywords: Association of Belarusian Student Organizations, Belarusian Students, Student Movement, International Student Confederation